PENGARUH TINGKAT PENDAPATAN, LITERASI ZAKAT DAN KEPERCAYAAN TERHADAP MINAT MASYARAKAT DALAM MEMBAYAR ZAKAT PADA BAZNAS PROVINSI LAMPUNG - Intan Suri Mahardika Pertiwi (Unitri Press, 2020)
The purpose of this study is to determine the effect of income levels, zakat literacy and trust in community interest in paying zakat at BAZNAS in Lampung province. This study uses a sampling technique with a sampling purvosipe method with a total of 100 respondents. The method of data collection is by questionnaire while the method of analysis is by multiple regression analysis with SPSS version 20. Soffware The results show (1) income and trust have a significant positive effect on the interest in paying zakat; (2) zakat literacy has no effect on people's interest in paying zakat at BAZNAS; (3) income, literacy of zakat and trust simultaneously affect the interest in paying zakat